Karakterisasi Sifat Fisik dan Kimia Asap Cair Hasil Pirolisis Limbah Potongan Rambut Manusia Asal Minahasa dengan KG-SM - Topol, Jovanca Rizky; Anom, I Dewe Ketut; Caroles, Joice D. (General Chemistry Journal, 2024)
Hair is a specialized derivative structure of the skin and is one of the defining characteristics of humans. Humans strive for the beauty of their hair, one of which is to change the hair model by cutting with various models. This phenomenon has resulted in the amount of hair waste generated every day from thousands of salons increasing rapidly. One of the natural materials that has been rarely utilized and difficult to decompose is human hair cut waste. The purpose of this study was to analyze the characteristics of physical and chemical properties of liquid smoke from pyrolysis of human hair waste from Minahasa. The method used to convert human hair waste into liquid smoke is pyrolysis. The physical properties of liquid smoke from pyrolysis of Minahasa human hair are: calorific value 8,166 cal/gr, viscosity 14.121 cSt, density 0.9837 g/ml, flash point 31oC, smoke point 172.4 oC, boiling point 139.2 oC, freezing point -14.6 oC. GC-MS analysis of liquid smoke liquid from pyrolysis of Minahasa native human hair pieces produced 30 peaks of chemical compounds. Based on these results, it can be concluded that pyrolysis of 1350 g of human haircut waste obtained a total yield of 105 g by weight of liquid smoke, with a percentage of 7.77%